Early indicators of success in a pharmacy curriculum: The role ofpre-professional science and mathematics courses - Crow, Robert T; Gaebelein, Claude J; Patel, Mona (Pharmacy Education, 2018)
This study identified courses in the pre-professional portion of the curriculum at the St. Louis College of Pharmacy that predicted success in the professional pharmacy curriculum, as measured by their impact on both cumulative grade point average (GPA) for their pre-professional work as well as their GPA before entering clinical externships. Transcripts of the class that started their pre-professional coursework in 1997 at the St. Louis College of Pharmacy underwent multiple regression modeling using SPSS software to analyze the effect of pre-professional science and math courses on pre-professional and pre-clinical academic performance. The basic math and science skills taught in general chemistry, biology, physiology, physics and organic chemistry had the strongest correlation with pre-professional success. Successful entry into the externship phase of the pharmacy curriculum depended primarily on biology, organic chemistry and physiology.